Macrophage migration inhibitory factor stimulates interleukin-17 expression and production in lymph node cells - Stojanović, Ivana (Blackwell Science Inc, 2009)
Interleukin (IL)-17 is a pro-inflammatory cytokine produced by recently described T helper type 17 (Th17) cells, which have critical role in immunity to extracellular bacteria and the pathogenesis of several autoimmune disorders. IL-6 and transforming growth factor (TGF)-β are crucial for the generation of Th17 cells in mice, while the production of IL-17 is supported by various cytokines, including IL-23, IL-1β, IL-21, IL-15 and tumour necrosis factor (TNF)-α. In this study, the influence of a multifunctional cytokine, macrophage migration inhibitory factor (MIF), on IL-17 production in mice was investigated. Treatment of lymph node cells (LNCs) with recombinant MIF up-regulated mitogen-stimulated IL-17 expression and secretion. Additionally, LNCs from MIF knockout mice (mif(−/−)) had severely impaired production of IL-17, as well as of IL-1β, IL-6, IL-23 and TGF-β. When stimulated with recombinant IL-1β, IL-23 or TNF-α, mitogen-triggered mif(−/−) LNCs were fully able to achieve the IL-17 production seen in wild-type (WT) LNCs, while the addition of IL-6 and TGF-β had no effect. Finally, after injection of mice with complete Freund's adjuvant, secretion of IL-17 as well as the number of IL-17-positive cells was significantly lower in the draining lymph nodes of mif(−/−) mice in comparison with WT mice. The effect of MIF on IL-17 production was dependent on p38, extracellular signal-regulated kinase (ERK), Jun N-terminal kinase (JNK) and Janus kinase 2/signal transducer and activator of transcription 3 (Jak2/STAT3), and not on nuclear factor (NF)-κB and nuclear factor of activated T cells (NFAT) signalling. Bearing in mind the contribution of MIF and IL-17 to the pathology of inflammatory and autoimmune disorders, from the results presented here it seems plausible that targeting MIF biological activity could be a valid therapeutic approach for the treatment of such diseases.